The Need for Cultivation and Crop Rotation of Chickpeas - Ma’muraxon, Atabayeva; oʻgli, Yuldashev Ziyodullo Murodjon (American Journal of Biology and Natural Sciences, 2024)
The change - weakening of soil bionitrification requires the wider use of leguminous crops in short rotation crop rotations on our irrigated lands and the practical implementation of intensive technologies for the cultivation of high-quality grain.